Healthcare 2022: overcoming the financial impact of covid-19 - Peter Kalina (Journal of Management and Science, 2021)
COVID-19 has had a tremendous impact on people around the world as well as on the global economy. It is a topic which cannot be ignored in any healthcare boardroom for the foreseeable future. While the pandemic profoundly transformed global healthcare, it also tested organizational change management processes and tested commitments to customer service and consistently exceeding customer expectations. In our new “disrupt or be disrupted” competitive market, dynamic strategies will portendbetter patient outcomes and an improved bottom-line.